2019
DOI: 10.4018/978-1-5225-8431-5.ch014
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Education

Abstract: Though only a dream a while ago, artificial intelligence (AI) has become a reality, being now part of our routines and penetrating every aspect of our lives, including education. It is still a field in its infancy, but as time progresses, we will witness how AI evolves and explore its untapped potential. Against this background, this chapter examines current insights and future perspectives of AI in various contexts, such as natural language processing (NLP), machine learning, and deep learning. For this purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…A growing body of literature has attempted to uncover the value of big data at different education levels, from preschool to higher education (Chen N.-S. et al, 2020). Several journal articles and book chapters have presented retrospective descriptions and the latest advances in the rapidly expanding research area from different angles, including systematic literature review (Zawacki-Richter et al, 2019;Quadir et al, 2020), bibliometric study (Hinojo-Lucena et al, 2019), qualitative analysis (Malik et al, 2019;Chen L. et al, 2020), and social network analysis (Goksel and Bozkurt, 2019). More details can be found in the previously mentioned reviews.…”
Section: The Position Formulationmentioning
confidence: 99%
“…A growing body of literature has attempted to uncover the value of big data at different education levels, from preschool to higher education (Chen N.-S. et al, 2020). Several journal articles and book chapters have presented retrospective descriptions and the latest advances in the rapidly expanding research area from different angles, including systematic literature review (Zawacki-Richter et al, 2019;Quadir et al, 2020), bibliometric study (Hinojo-Lucena et al, 2019), qualitative analysis (Malik et al, 2019;Chen L. et al, 2020), and social network analysis (Goksel and Bozkurt, 2019). More details can be found in the previously mentioned reviews.…”
Section: The Position Formulationmentioning
confidence: 99%
“…Zawacki-Richter, Marín, Bond and Gouverneur [33] investigated research on AI in higher education and they critically draw attention to most of the papers' "lack of critical reflection of challenges and risks of AIEd, the weak connection to theoretical pedagogical perspectives, and the need for further exploration of ethical and educational approaches in the application of AIEd in higher education." In their review study, Goksel and Bozkurt [34] identified three broad themes, namely, adaptive learning, personalization and learning styles, expert systems and intelligent tutoring systems, and AI as a future component of educational processes. However, they further noted that though AI in education has great potential, it would be misleading to accept it superior by default and researchers "need to develop a critical stance before fully integrating AI into educational processes.…”
Section: Related Literaturementioning
confidence: 99%
“…It is reported that use of AI-generated data through learning analytics and intelligent tutoring systems improve student performance [57]. Due to significant progress in theory and practice derived from the application of AI [12] and the potentials in educational data mining, learning analytics [50,58], it is further argued that AI is a future component of educational processes [34].…”
Section: T-sne Text-mining and Social Network Analysismentioning
confidence: 99%
“…Due to the outbreak of COVID-19, filling forms, upgrading files, cross-referencing documents can be used in this case, as the need arises. With this advantage, many firms will use AIenabled data management systems to identify extortion, avoid cyber security threats and enhance their overall business activities during the pandemic (Goksel and Bozkurt, 2019;Di Vaio et al 2020).…”
Section: Conclusion and Implications Of The Studymentioning
confidence: 99%